2020
DOI: 10.1002/eji.201948497
|View full text |Cite
|
Sign up to set email alerts
|

Migration of murine intestinal dendritic cell subsets upon intrinsic and extrinsic TLR3 stimulation

Abstract: Initiation of adaptive immunity to particulate antigens in lymph nodes largely depends on their presentation by migratory dendritic cells (DCs). DC subsets differ in their capacity to induce specific types of immunity, allowing subset-specific DC-targeting to influence vaccination and therapy outcomes. Faithful drug design, however, requires exact understanding of subset-specific versus global activation mechanisms. cDC1, the subset of DCs that excel in supporting immunity toward viruses, intracellular bacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
10
1
Order By: Relevance
“…This contrasts with previous findings indicating that TNF-α can increase the influx of lymphocytes into draining LN and, in some cases, can also block lymphocyte exit [17][18][19]39,44]. In addition, TNF-α signaling can drive migration of peripheral DC to the draining LN at steady state or in response to the TLR ligands poly(I:C) or R848 [45][46][47][48]. However, LN hypertrophy induced by Anopheles mosquito bite is independent of TNFα [49] and genetic ablation of the TNFR1 has no effect on the PP hypertrophy observed in response to Salmonella infection [22].…”
Section: Discussioncontrasting
confidence: 92%
“…This contrasts with previous findings indicating that TNF-α can increase the influx of lymphocytes into draining LN and, in some cases, can also block lymphocyte exit [17][18][19]39,44]. In addition, TNF-α signaling can drive migration of peripheral DC to the draining LN at steady state or in response to the TLR ligands poly(I:C) or R848 [45][46][47][48]. However, LN hypertrophy induced by Anopheles mosquito bite is independent of TNFα [49] and genetic ablation of the TNFR1 has no effect on the PP hypertrophy observed in response to Salmonella infection [22].…”
Section: Discussioncontrasting
confidence: 92%
“…Differences in the expression level of the dsRNA pattern recognition receptor (PRR) TLR3 between neonates and adults have previously been discussed to account for the pronounced susceptibility to RV infection by neonates ( 19 ). cDC1 uniquely express high levels of TLR3 ( 20 ), leading us to hypothesize that optimal CD8 T cell priming in response to RV infection may require dsRNA sensing through TLR3.…”
Section: Resultsmentioning
confidence: 99%
“…Downstream signaling cumulates in the induction of type I IFNs, which were shown to orchestrate gene expression profile changes within DCs upon PRR sensing in an autocrine manner ( 24 ). We have previously shown that cDC1 depend on the ability to sense type I IFN for migration and activation in response to poly(I:C) ( 20 ). Furthermore, microbiota-induced steady-state type I IFN signaling in the intestines poises DCs into an immune inductive state, while the absence of type I IFN sensing renders intestinal DCs unable to prime effector T cells ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although cDC1s express higher amounts of TLR3, which recognizes Poly (I:C), these cells are essentially matured through type I interferons after in vivo injection of Poly (I:C) ( Edwards et al, 2003 ; Trumpfheller et al, 2008 ). On the contrary, cDC2s, which do not express TLR3, are stimulated via another pathway, TNF-α and IL-6 synergically stimulate the up-regulation of costimulatory molecules and consequently the migration of cDC2s in response to Poly (I:C) ( Edwards et al, 2003 ; Garcias Lopez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%